Article RETRACTED: include references that are unrelated to the subject of the article and/or the context in which they are cited Entrenamiento de resistencia y variables fisiológicas: efectos en jugadores de voleibol de subélite (Endurance training and physiological variables: effects on sub-elite volleyball players): Article RETRACTED: include references that are unrelated to the subject of the article and/or the context in which they are cited - Latino, Francesca; Martinez-Roig, Rosabel; Susanto, Nugroho; Setyawan, Hendra; Anam, Khoiril; Saraiello, Emma; Tafuri, Domenico; Tafuri, Francesco (Retos, 2024)
El voleibol se percibe como un deporte físicamente exigente que implica cambios rápidos de velocidad, desaceleración y alteraciones bruscas en la dirección del movimiento. Se ha enfatizado que los atributos fisiológicos como el VO2max, el PIF, el PEF y el FVC juegan un papel crucial en el rendimiento atlético de las personas que participan en deportes dinámicos, ayudándolos a manejar de manera efectiva situaciones críticas. Por lo tanto, el objetivo de esta investigación fue evaluar el impacto del entrenamiento de resistencia sobre los parámetros fisiológicos en atletas de voleibol. Se llevó a cabo un ensayo controlado aleatorizado con 24 jugadores varones (edad media 21,58; DE±2,46 años). La evaluación de las características fisiológicas implicó la utilización de un espirómetro seco para la medición del VO2máx y la prueba de aptitud multietapa para evaluar el PIF, el PEF y el FVC. Se ejecutó un análisis de Anova de dos vías para determinar cualquier disparidad en los parámetros fisiológicos desde el pre-test hasta el post-test. Los resultados indicaron variaciones notables en los rasgos fisiológicos (VO2max, PIF, PEF y FVC) entre los participantes de voleibol después de la implementación del régimen de intervención Tabata. Estas métricas son fundamentales para mejorar las capacidades fisiológicas para lograr rendimientos atléticos superiores. A la hora de diseñar regímenes de entrenamiento, es imprescindible tener en cuenta los elementos fisiológicos funcionales alineados con las demandas específicas del deporte. Palabras clave. VO2max; fisiología; deporte; ejercicio; Entrenamiento de Tabata. Abstract. Volleyball is perceived as a physically demanding sport that involves rapid changes in speed, deceleration, and abrupt alterations in movement direction. It has been emphasized that physiological attributes such as VO2max, PIF, PEF, and FVC play a crucial role in the athletic performance of individuals participating in dynamic sports, aiding them in effectively managing critical situations. Hence, the aim of this research was to evaluate the impact of endurance training on physiological parameters among volleyball athletes. A randomized controlled trial was carried out with 24 male players (mean age 21,58; SD±2,46 years). The assessment of physiological characteristics involved the utilization of a dry spirometer for VO2max measurement and the Multistage Fitness Test for assessing PIF, PEF, and FVC. A two-way Anova analysis was executed to ascertain any disparities in physiological parameters from pre-test to post-test. The results indicated notable variances in physiological traits (VO2max, PIF, PEF, and FVC) among volleyball participants following the implementation of the Tabata intervention regimen. These metrics are instrumental in enhancing physiological capabilities to attain superior athletic performances. When designing training regimens, it is imperative to consider physiological functional elements aligned with the specific demands of the sport. Key words. VO2max; physiology; sport; exercise; Tabata training.